Managing Socio‐Ecological Systems to Achieve Sustainability: A Study of Resilience and Robustness - Domptail, Stephanie; Easdale, Marcos Horacio; Yuerlita (Wiley, 2019)
Growing symptoms of the mismanagement of socio‐ecological systems (SESs) show that the long‐term existence of these systems is threatened. SES management improvement is the aim of many policy measures. But how successful are these various simultaneous policy measures in achieving the sustainable management of SESs? A framework for analysing policy measures and the management actions of land users was developed by Leach et al. (2010): the authors postulate that the sustainability of an SES depends on four system properties – stability, resilience, durability and robustness – and that external shocks and stresses affect these properties differently. The aim of this contribution is to identify the strengths and weaknesses of the approach by applying it to three case studies, in Namibia, Argentina and Indonesia. We found that (1) more actions were directed towards resilience and robustness than towards command and control, (2) actions directed at stability and durability were generally undertaken at the national level and (3) the introduction of the concept of robustness to illustrate the property of adaptability enables the identification of trade‐offs among properties, but (4) issues of ecological degradation were difficult to address explicitly. We consider that the framework can make a useful contribution to policy making by framing the impact of a given intervention on SESs on the four key system properties. Yet, the framework provides a structure to make ex‐post assessment of SES management or to formulate assumptions about potential synergies/trade‐offs among impacts on system properties. However, we suggest using it as complementary to other policy impact assessment methods